ICJ Advisory Opinion on Legal Consequences of the Separation of the Chagos Archipelago From Mauritius in 1965 (Chagos Advisory Opinion): A Critical Analysis (Dhaka University Law Journal, 2023)
The Chagos AO is a milestone in the history of decolonization which certainly added some narratives to the jurisprudence of the right to selfdetermination, rules of identification of customary international law, and the practice of the ICJ in relation to its jurisdiction on an advisory opinion. Similarly, ICJ had missed dealing with the human rights of the inhabitants of Chagos Archipelago which was the subject matter of the opinion, whether the right to self-determination qualifies as peremptory norms or not, etc. This paper critically discusses the approach taken by the World Court in this case in five sections, e.g., the judicial propriety in the AO, the territorial aspect of the right to selfdetermination, the right to self-determination and customary international law, the right to self-determination and jus cogens, and human rights of the Chagossians.Dhaka University Law Journal, Vol. 33(1), 2023 P.95-110